P220 Patient-entered symptoms scores collected using a new IBD patient portal correlate closely with clinical assessment and can optimise delivery of IBD care. (27th May 2021) - Carlson, S; Harrow, P; McCartney, S
Abstract: Background: Patient healthcare portals can empower IBD patients by allowing access to their electronic health record and provide opportunities for active participation in their care. We built 3 patient-entered symptom questionnaires in EPIC MyChart using existing validated IBD symptom scores (HBI, SCCAI, IBD Control). Patients were invited to complete these prior to clinic using the MyChart patient portal. In this study we examine the feasibility and accuracy of patient entered scores compared to the physician's impression of disease activity and the potential impact on healthcare delivery. Methods: Between September 2020 and January 2021 consecutive patients were invited to complete 2 questionnaires reporting disease activity on the EPIC MyChart portal using the IBD Control (Bodger et al. 2014) and either HBI or SCCAI (for Crohn's disease and UC respectively). Only patients who completed these scores were included in this study. A retrospective review of the notes was completed to determine the physician's impression of disease activity and actions taken by the physician in the outpatient clinic. Results: 107 patients with Crohn's and 80 with UC were included in the study. 60% of CD and 56% of UC patients were in remission by HBI (<5) or SCCAI (<3). Patient reported disease activity correlated well with clinical impression of disease activity. 88% of CD patients and 98% of UC patients in HBI or SCCAI remission were also deemed to be in remission on physician's clinical impression (r= 0.54, p <0.001 and r= 0.74, p <0.001). Both CD and UC had lower rates of remission by IBD Control (49% and 53%). This score also captures fatigue and mood. Furthermore, the IBD Control identified a specific question to be addressed at the upcoming clinic visit for 76% of patients with CD and 64% with UC. Importantly, 24% of all UC patients (n=19) in remission by SCCAI and IBD Control, had no questions they wanted addressed, and all of these patients had no further actions triggered by clinic attendance. Conversely in the 18% patients with moderate to severe disease by HBI or SCCAI, 50% required a blood test or calprotectin prior to further clinical decisions. Conclusion: Patient-entered symptom scores correlate closely with physician's impression of disease activity and patients are able to accurately record these using the EPIC MyChart portal. Importantly, it is possible to identify a cohort of patients who are well, where there are opportunities to optimise follow-up, and conversely a group of patients with active disease where key investigations can be arranged prior to clinical review to prevent delays in treatment. These patients can also be prioritised for face-to-face clinics, at a time when reducing social contacts is imperative.